PROBLEMS RELATED TO INCREASING THE STABILITY OF THE BANKING SYSTEM - Kamalov Shuxrat Kamalovich (Journals Park Publishing, 2024)
The bank's equity capital is the most important basis of the bank's activity, and it is the source of financing economic and financial activities in the establishment of the bank. In the future, bank capital will ensure development, work as a source of risk coverage. Equity capital of banks ensures the stability of the banking sector and its development.
Keywords: bank equity, financial activity, financial institutions, bank capital base.